An Interface Strip Preconditioner for Domain Decomposition Methods: Application to Hydrology - Paz, Rodrigo Rafael (2005)
In this paper, the efficiency of a parallelizable preconditioner for domain decomposition methodsin the context of the solution of non-symmetric linear equations arising from discretization of the Saint-Venant equations, is investigated. The proposed interface strip preconditioner (IS) is based on solving a problem in a narrow strip around the interface. It requires much less memory and computing time than classical Neumann–Neumann preconditioner, and handles correctly the flux splitting among sub-domains that share the interface. The performance of this preconditioner is assessed with an analytical study of Schur complement matrix eigenvalues and numerical experiments conducted in a parallel computational environment (consisting of a Beowulf cluster of 20 nodes).